2002
DOI: 10.1176/appi.ajp.159.5.860
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Care Quality Under Managed Care in the United States: A View From the Health Employer Data and Information Set (HEDIS)

Abstract: Better general medical care, transparency of reporting, and commitment of fiscal resources to clinical care predicted better mental health care performance for U.S. HMOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
2
20
0
3
Order By: Relevance
“…Guideline-concordant depression treatment is associated with improvements in depression severity, better clinical and mental health quality of life outcomes, and higher rates of employment (Fortney et al 2001;Schoenbaum et al 2002). However, many patients fail to receive guideline-recommended levels of care (Druss et al 2002;McCarthy et al 2007;Robinson et al 2006).…”
mentioning
confidence: 99%
“…Guideline-concordant depression treatment is associated with improvements in depression severity, better clinical and mental health quality of life outcomes, and higher rates of employment (Fortney et al 2001;Schoenbaum et al 2002). However, many patients fail to receive guideline-recommended levels of care (Druss et al 2002;McCarthy et al 2007;Robinson et al 2006).…”
mentioning
confidence: 99%
“…In their unsettling Quality Chasm series, the Institute of Medicine reported on the large gap that exists between what is known to be effective care for mental health conditions and the treatment that is actually delivered (IOM 2001a(IOM , 2006(IOM , 2007. Research has shown, for example, that managed care companies deliver mental health care in accordance with standards of care only 48% of the time compared with 69% of the time for general health care (Druss et al 2002) and rates of provider treatment guideline adherence for mental health care are below 50% on average, and in some cases as low as 20% (IOM 2006). In particular, mental health providers' expertise in detecting and treating children's serious mental illness has been found lacking (GAO 2003).…”
Section: Limitations In Treatment Availability and Qualitymentioning
confidence: 99%
“…Yet the hypothesized relationship is likely more direct, hence testable by the designs used in these studies. Given that continuity of care is a suggested ethical aim of service delivery (Thornicroft & Tansella, 1999) and a common criterion for evaluating performance of mental health care systems (Druss, Miller, Rosenheck, Shih, & Bost, 2002;Rosenheck & Cicchetti, 1998), a review of relevant research is timely. The aim of this paper is to reexamine these key studies to summarize the evidence on the association between systems integration and continuity, identify strategies associated with increased continuity and suggest areas for further research.…”
Section: Introductionmentioning
confidence: 99%